Effectiveness various kind traps for insect control based environmental friendly ways. Issue 1 (October 2020) - Aminah, S N; Abdullah, T; Nasruddin, A; Sari, N A
Abstract: The purpose of research is to study the effectiveness of various kind traps for insect control based environmental friendly in kangkong field. The experimental research was held in Pangngai village, Bantaeng Regency, South Sulawesi, Indonesia. Based insects collection in the Serimpi cultivar, there are 60 total individuals were collected divided into 8 order (Coleoptera, Hemiptera, Orthoptera, Isoptera, Lepidoptera, Diptera, Hymenoptera and Mantodea) including in the 22 families as pests, predators and decomposers. The findings of various kind traps applied was showed insect net method collected more pest insect (19 individual) than pitfall trap (11 individual) and yellow trap (10 individual), respectively. Based the research data was showed that insect net more effective in collected insects (45%) than pitfall trap (32%) and yellow trap (23%), respectively. The total harvest was showed the increasing number and quality of kangkong about 6 kg, more higher on the past (3-4 kg). In the future, the result of the research is very useful information for apply insect control based environmentally friendly ways.